Meta-analysis of the antecedent and consequent constructs of materialism - Santini, Fernando de Oliveira (2017)
Purpose – Materialism has been gaining ground in the academic field, especially from the 1980s on, given the relevance of understanding sentiments connected to possessing and acquiring goods. Thus, this meta-analysis was carried out to assess the antecedents and consequents of materialism.Design/methodology/approach – Based on a systematic review, we gathered a total 77 articles that examined those aspects, generating 99 effects-sizes and a cumulative sample of 40,288 studied individuals.Findings – The antecedents of materialism that showed a significant relationship with this construct were: perceived hedonic value, interpersonal influence, life satisfaction, and income. As for the consequents, we observed significance for purchase intention, impulsive buying, compulsive buying, conspicuous consumption, status consumption, and consumer involvement. Regarding the moderating effect, we observed that small samples produce greater effects. Furthermore, for the relationship between materialism and purchase intention, there are stronger effects for surveys conducted in Western countries. Originality/value – Based on the methodology applied in this study, we expected a solid and generalizable contribution regarding construct materialism.